PENGARUH FINTECH DAN INKLUSI KEUANGAN TERHADAP PERKEMBANGAN UMKM DI KABUPATEN TANJUNG JABUNG TIMUR - Rizki Nanda Saputra Nanda Saputra; Rofiqoh Ferawati (ICONS: Islamic Economics Journal, 2026)
This study aims to determine the impact of Fintech and financial inclusion on the development of MSMEs in East Tanjung Jabung Regency. This research is descriptive quantitative. The sample in this study was 100 MSMEs, using purposive sampling. Data analysis used SPSS 30. The results show that 1) the Fintech variable has a positive and significant influence on the development of MSMEs in East Tanjung Jabung Regency. 2) The financial inclusion variable has a positive and significant influence on the development of MSMEs in East Tanjung Jabung Regency. 3) The Fintech and financial inclusion variables simultaneously have a positive and significant influence on the development of MSMEs in East Tanjung Jabung Regency. The coefficient of determination of the independent variable on the dependent variable is 41.7%.